ASEAN 2.0 : ICT, Governance and Community in Southeast Asia - Lallana, Emmanuel C. (Book collections on Project MUSE., 2012)
This study argues that the extensive use of Information and Communications Technology (ICT) by the Association of Southeast Asian Nations (ASEAN) would: ((1) enhance policy coordination within the intergovernmental organization; (2) promote inclusive regionalism by providing new avenues for broader stakeholder participation in regional affairs; (3) help develop a stronger regional identity, particularly among the young; and (4) improve ""network management"" or coordination of the collaborative activities of the member states. But this study is not merely about making ASEAN more effective. By.